A Crime Script Analysis of Fatal Police Shootings in New York - Silva, Jason (Criminology, criminal justice, law & society, 2022)
This study provides a crime script analysis of fatal police shootings in New York from 2013 to 2020. This work examines incident rates and subject demographics, as well as the initial situation context, subject-officer encounter, and incident conclusion stages of fatal police shootings. Findings identify an average of 19 incidents per year (N = 152). Subjects were most commonly male, aged 26-35, and Black. Situations initiating police presence often involved violent crimes, mental health/welfare checks, and domestic disputes. During the subject-officer encounter, subjects were often armed with a weapon, and half were armed with a firearm. Despite these potentially dangerous weapons, incidents rarely concluded with non-subject deaths or victim injuries. A discussion of findings highlights implications for understanding and addressing fatal police shootings including curbing illegal gun obtainment, pairing officers with crisis intervention teams and mental health workers, using less-lethal devices, and strengthening officer field tactics.